2008
DOI: 10.17656/jzs.10190
|View full text |Cite
|
Sign up to set email alerts
|

Milk Production in Awassi Sheep and their Crosses with Assaf under Accelerated Lambing System

Abstract: At the Sheep Breeding Station, IPA Agricultural Research Center, milk production was investigated in 92 Iraq Awassi (AW) and 95 Assaf x Awassi (AA) ewes under accelerated lambing system , together with effects of age and body weight of ewe , lambing season and sex by litter size of lamb using General Linear Model (GLM) procedure . The overall means of milk yield and lactation period were 85.64 kg and 132.36 days, respectively. AA ewes surpassed significantly AW ewes in milk yield (99.15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 9 publications
3
4
0
Order By: Relevance
“…Daily milk production of ewes in February (478.09 gm) was differed significantly (p≤0.05) as compared with January (458.95 gm) and December (475.60 gm). Similar results were reported by (Jalal et al, 2016 andBalisany, 2016), this result could be attributed to changes in the environmental conditions, particularly in ambient temperature together with the availability of feeds during different lambing months (Alkass, 2009). The ewes with male lams had higher milk production (488.57 gm) than did those with female (451.29 gm) lambs the differences being significant (P≤0.05).This may attributed to the fact that males are usually bigger than females and need higher nutrients, thus induce mothers to produce more quantities of milk, these findings were in agreement with those reported by (Owen,1976;Ploumi andEmmanouilidis,1999 andAl-sherwani, 2013) ,and on the other hand (Al-samarai et al, 2014 andJalal et al, 2016), showed no significant effect of sex on milk production.…”
Section: Resultssupporting
confidence: 89%
“…Daily milk production of ewes in February (478.09 gm) was differed significantly (p≤0.05) as compared with January (458.95 gm) and December (475.60 gm). Similar results were reported by (Jalal et al, 2016 andBalisany, 2016), this result could be attributed to changes in the environmental conditions, particularly in ambient temperature together with the availability of feeds during different lambing months (Alkass, 2009). The ewes with male lams had higher milk production (488.57 gm) than did those with female (451.29 gm) lambs the differences being significant (P≤0.05).This may attributed to the fact that males are usually bigger than females and need higher nutrients, thus induce mothers to produce more quantities of milk, these findings were in agreement with those reported by (Owen,1976;Ploumi andEmmanouilidis,1999 andAl-sherwani, 2013) ,and on the other hand (Al-samarai et al, 2014 andJalal et al, 2016), showed no significant effect of sex on milk production.…”
Section: Resultssupporting
confidence: 89%
“…Lactation period averaged 169.33 and 140.28 days for ewes maintained in restricted and continuous suckling system, respectively; and the difference between them is significant (p < 0.05) (Table 1). The length of lactation recorded herein is longer than that reported earlier by other workers on Awassi ewes (3,9,14,19) as well as for karadi ewes (2), but it is almost similar to those indicated by Alkass and A keryi. (1) for Awassi (169.66 daya) and karadi ewes (168.71 days).…”
Section: Resultssupporting
confidence: 77%
“…Results revealed that the overall means of preweaning, post-weaning, total, and commercial milk yield averaged 57.25 ± 3.22, 65.66 ± 6.63, 122.91 ±7.56 and 75.52 ± 7.72 L, respectively. Moreover, total milk yield recorded herein by native ewes is higher than those reported earlier for the Awassi in Iraq (3,14) as well as it is higher than those recorded earlier for karadi ewes (2,4,21).However, such value is very close to those found earthier for Awassi ewes ( 126.05 L) and karadi ewes (126.39 L) by Alkass and Akreyi (1). Such differences in yield could be attributed to the genetic make-up of the animals, as well as conditions of ewes and feeding and management practices followed in different farms.…”
Section: Resultssupporting
confidence: 59%
“…In a previous research conducted in Iraq by [20], no statistically significant impact of the lambing month was observed on the milk protein % and fat % in Karadi, Awassi, and Hamdani ewes. This outcome may be ascribed to variations in environmental factors, specifically fluctuations in ambient temperature and the varying accessibility of feeds across different lambing months [21].…”
Section: Month Of Birthmentioning
confidence: 99%